Etiopathogenesis of Nonalcoholic Steatohepatitis: Role of Obesity, Insulin Resistance and Mechanisms of Hepatotoxicity - Praveen Guturu; Andrea Duchini (International Journal of Hepatology)
Incidence of nonalcoholic fatty liver disease is increasing with an estimated prevalence of 20–30% in developed nations. This is leading to increased incidence of chronic liver disease, cirrhosis, and hepatocellular cancer. It is critical to understand the etiology and pathogenesis of any disease to create therapeutic targets and develop new treatments. In this paper we discuss the etiology and pathogenesis of nonalcoholic steatohepatitis with special focus on obesity, role of insulin resistance, and molecular mechanisms of hepatotoxicity.